Sphaeranthus gomphrenoides (Compositae): New record to Asia with its identity, typification, and distribution - Nimbalkar, Varsha V.; Sharma, Oshin A.; Girdhari, Milind M.; Sardesai, Milind M. (Phytotaxa, 2021)
Sphaeranthus gomphrenoides is reported as new to Asia, and the details of its identification, typification, and distribution are provided here along with the designation of a lectotype. The article includes an amended description, a line drawing illustration and a detailed photo plate of the plant with an artificial key to the Indian Sphaeranthus species.